2002
DOI: 10.1161/01.cir.0000027138.07524.38
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Survival and Hemodynamics After Endothelin-A Receptor Antagonism and Angiotensin-Converting Enzyme Inhibition in Rats With Chronic Heart Failure

Abstract: Background-In patients with congestive heart failure (CHF) receiving ACE inhibitors, acute administration of selective endothelin (ET) antagonists additionally improves systemic and cardiac hemodynamics. We investigated, in a rat model of CHF, whether such acute synergistic effects are sustained and accompanied, in the long term, by an additional limitation of left ventricular remodeling or an increase in survival. Methods and Results-Rats were subjected to coronary artery ligation and treated for 3 or 9 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 49 publications
3
34
1
Order By: Relevance
“…ET1 was shown to be elevated in blood samples of HF patients, to predict outcome and to play a crucial role for adverse cardiac remodeling (6). In 1996, it was demonstrated that endothelin receptor inhibition is cardioprotective in a preclinical model of HF (7), which was supported by others (8)(9)(10). However, despite convincing preclinical data, unspecific ET1 receptor and specific ET A inhibitors (ET A i) showed no beneficial effects in clinical HF trials (11,12).…”
mentioning
confidence: 90%
“…ET1 was shown to be elevated in blood samples of HF patients, to predict outcome and to play a crucial role for adverse cardiac remodeling (6). In 1996, it was demonstrated that endothelin receptor inhibition is cardioprotective in a preclinical model of HF (7), which was supported by others (8)(9)(10). However, despite convincing preclinical data, unspecific ET1 receptor and specific ET A inhibitors (ET A i) showed no beneficial effects in clinical HF trials (11,12).…”
mentioning
confidence: 90%
“…We produced MI by ligation of the left coronary artery in 11 week-old male Wistar rats, anesthetized with Ketamine and Xylazine (60 and 5 mg/kg, respectively, intraperitoneally) [33]. MI resulted in a mean 41% infarct size ( Table 1).…”
Section: Induction Of Myocardial Infarction (Mi) In Ratsmentioning
confidence: 99%
“…Transthoracic Doppler echocardiographic studies, using an echocardiographic system (HDI 5000, ATL, USA) equipped with an 8.5 MHz probe, were performed in anesthetized rats (Brietal™; 50 mg.kg -1 , intraperitoneally) [33]. LV diameters were measured by the American Society of Echocardiology leading-edge method from at least 3 consecutive cardiac cycles [34].…”
Section: Nac Treatmentmentioning
confidence: 99%
See 2 more Smart Citations